Strategi Strategi mitigasi sepuluh risiko bank syariah: pendekatan studi literatur dan evaluasi praktik terbaik mitigasi risiko - Atoillah, M (Maliki Interdisciplinary Journal, 2025)
This study aims to identify and classify ten main types of risks faced by Islamic banks and examine relevant mitigation strategies based on literature studies and best practices in the industry. Using a qualitative approach through literature studies, this study found that Islamic banks face more complex risks than conventional banks, such as financing, liquidity, operational, market, legal, compliance, strategic, reputational, yield, and sharia risks. Each risk is analyzed based on its source, impact, and mitigation strategy, which are grouped into three main approaches: avoidance, control, and risk transfer. In addition, this study emphasizes the importance of best mitigation practices, such as the integration of information technology in early warning systems and stress testing, strengthening the role of the Sharia Supervisory Board, transparency of risk reporting, and harmonization of regulations with international standards. These findings are expected to be a practical reference for industry players and regulators in building a comprehensive and sharia-compliant risk management system, as well as strengthening the resilience and sustainability of Islamic banks amidst the challenges of the global economy and dynamic regulations.